Phosphorus content in the soil microbial biomass under Brachiaria decumbens Stapf - da Fonseca, Monica Cristina C.; de Almeida, Dejair Lopes; De-Polli, Helvécio; Fernandes, Manlio Silvestre (Pesquisa Agropecuaria Brasileira, 1995)
Following a long-term experiment on the growth of Brachiaria decumbens fertilized with different sources of phosphorus applied at different times, a study was performed to estimate the phosphorus in the microbial biomass using the fumigation-extraction method. The treatments were: no P fertilization (P0), rock phosphate incorporated 60 days before planting (RFpl), rock phosphate 60 days before planting and triple superphosphate applied 3 years later (RFpl + STcob), superphosphate at planting (STpl), superphosphate at full leaf cover (STcob), and superphosphate at planting and 3 years later (STpl + STcob). The addition rate at each of the two stages of fertilizer application was equivalent to 87 kg P/ha. The microbial P increased from 7.7 to 13.7 mg P/kg soil when the soil was fertilized with superphosphate, either at planting, or three years later at full leaf cover, resulting in an increase in the P concentration in the biomass from 10.6 to 21.2 g P/kg biomass in the same treatments. There was a tendency for the application of superphosphate to cause a decrease in the C:P ratio of the biomass independent of the date of application. Thus, the plots fertilized with superphosphate at planting and again 3 years later, did not result in any increase in the P content in the microbial biomass when compared with the plots fertilized only at planting, showing that even after 5 years of growth of Brachiaria the soil microbial biomass was found to be higher in P than in the treatment where there was no P fertilization. The microbial P was shown to be a promising parameter for studies of the fate and dynamics of P in the soil.